A Contribution to the Sensor Network Management for Context Awareness in Ubicomp - Souza, Rodrigo Santos de; Lopes, João Ladislau Barbará; Geyer, Cláudio Fernando Resin; Fleischmann, Ana Marilza Pernas; Yamin, Adenauer Corrêa; Gadotti, Gizele Ingrid (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
One of the central aspects of Ubiquitous Computing (Ubicomp) is associated with tight integration between computer systems and the environment. In this sense, one of the main research challenges in the area is to provide mechanisms for context awareness that promote the development of applications that respond itself according to the dynamics of the physical environment of user's interest. This paper presents the EXEHDA-SN, a software architecture managed by rules that provides the interaction of UbiComp systems with the physical environment by sensors networks and actuators. This work is being developed as part of research efforts related to EXEHDA Middleware. To assess the functionality of the EXEHDA-SN, we present a case study in agricultural area, highlighting the prototypes and tests performed.